Does Independent Directors Earn Higher Compensation? - Robin Robin; Claudio Esmeraldo Winarno (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
This study aimed to explore the effect of independent directors of a publicly listed firm in Indonesia on their total compensation. Following the footsteps of other developing countries, Indonesian corporations have recently appointed more independent directors. Independent directors are thought to play an important role in determining executive compensation. This Paper takes a sample of 50 publicly listed firms in Indonesia ranked as the “best of the best firm in 2020” by well-known business magazine, Forbes. Those 50 firms were filtered by their financial performance and their practice of good corporate governance. 50 Financial reports spanning from the year 2015 – 2019 listed in the list were collected to analyze the relationship between the number of independent directors and total compensation received. The results of the studies suggest that the number of independent directors does influence their total compensation received. There is a significant positive relationship between the number of independent directors in a board structure and their total compensation received.